ANALISIS PERILAKU INDIVIDU DALAM ORGANISASI: FAKTOR KINERJA DAN DINAMIKA TIM DI LINGKUNGAN KERJA MODERN - Eko Julianto Wibowo; Prim Masrokan Mutohar (Al Madjid : jurnal Pendidikan Islam, 2026)
This research focuses on analyzing individual behavior within organizations, as well as the various variables that influence team performance and dynamics in today's workplace. Essentially, achieving an organization's collective goals depends heavily on how individuals within it behave, a behavior typically shaped by crucial factors such as motivation, work environment conditions, and available social support. By delving into the behavioral characteristics and interaction patterns within teams, management will have a strong foundation for formulating more targeted strategies to boost productivity. In addition to these internal factors, the presence of technology in the modern era also plays a significant role in shaping individual and group behavior. While adapting to new systems often presents challenges, appropriate technology integration has been shown to have a significant positive impact, particularly in strengthening collaboration and overall work efficiency.